2016
DOI: 10.1097/ijg.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “IS” Rule to Differentiate Glaucomatous Eyes From Normal

Abstract: The ISNT rule alone has a high sensitivity but relatively low specificity. Application of the IS rule in eyes with increased CDR yields a much higher specificity for differentiating normal from more advanced glaucomatous eyes. A combination of different features of the optic disc (increase of CDR and ISNT or IS rule) improves the specificity of optic disc evaluation for glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
5
22
1
3
Order By: Relevance
“…In a normal population of 92 Chinese subjects, Wang et al 19 found that 9 out of 92 subjects (10%) had a nasal rim that was the widest compared to all the other rims, while Harizman et al 13 also reported in their study that 5 out of 66 normal subjects (7.6%) had nasal rim that was thicker than the inferior rim. Additionally, we also found that the nasal rim was wider than the superior rim in 29.4% of subjects and that the nasal rim was narrower than the temporal rim in 14.7% of subjects; and these percentages are consistent with previously reported rates for normal subjects of 28% – 36% 14, 19 and 14% – 29%, 14, 19 respectively. A possible reason for the high variability in nasal rim order and hence the low fulfillment rate of the ISNT rule in our study is that, although the central retinal vessel was not considered as part of the neuroretinal rim during disc assessments, there often is partial obscuration of the nasal rim by these large retinal vessels, which would make evaluation of the nasal rim width ranking more variable.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In a normal population of 92 Chinese subjects, Wang et al 19 found that 9 out of 92 subjects (10%) had a nasal rim that was the widest compared to all the other rims, while Harizman et al 13 also reported in their study that 5 out of 66 normal subjects (7.6%) had nasal rim that was thicker than the inferior rim. Additionally, we also found that the nasal rim was wider than the superior rim in 29.4% of subjects and that the nasal rim was narrower than the temporal rim in 14.7% of subjects; and these percentages are consistent with previously reported rates for normal subjects of 28% – 36% 14, 19 and 14% – 29%, 14, 19 respectively. A possible reason for the high variability in nasal rim order and hence the low fulfillment rate of the ISNT rule in our study is that, although the central retinal vessel was not considered as part of the neuroretinal rim during disc assessments, there often is partial obscuration of the nasal rim by these large retinal vessels, which would make evaluation of the nasal rim width ranking more variable.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, for disc photo assessments, having only 37% of disc photos obey the ISNT rule is lower than previously reported rates of 52% to 79% 13, 14, 19 in studies that also evaluated the neuroretinal rim width using disc photographs in the normal population. By examining the relationship between the nasal quadrant and the other quadrants with respect to the expected trend of the ISNT rule, we found that a main reason that the ISNT rule was not valid was because of considerable variation in the rim order of the nasal quadrant, in which 10.9% of subjects had a rim width that was wider nasally than inferiorly (Figure 3).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations